“I Like the One With Minions”: The Influence of Marketing on Packages of Ultra-Processed Snacks on Children's Food Choices - Sato, Priscila de Morais; Leite, Fernanda Helena Marrocos; Khandpur, Neha; Martins, Ana Paula Bortoletto; Mais, Laís Amaral (Frontiers in Nutrition, 2022)
Objectives: to assess the most consumed school snacks using free listing and understand how marketing strategies on food labels influenced children’s perceptions of snacks via focus groups. Design: free lists and semi-structured focus group interviews Setting: São Paulo, Brazil Participants: Sixty-nine children. Phenomenon of interest: children’s perceptions of food labels Analysis: Food groups mentioned on free lists were analyzed for their frequency and priority of occurrence. Focus groups were analyzed through content analysis. Results: Juices and chips were the most salient snacks, with availability and flavor as reasons for their consumption. Children found images on labels appealing, which created desire for the food, although could be deceptive. Snacks perceived as healthy were encouraged by parents and children could more easily convince them to buying snacks with health claims. Colors and brands were important to catch children’s attention and make the snack recognizable. Television commercials and mascots reinforced marketing strategies on labels. Conclusions and implications: Our results point to the need for public health strategies to deal with the obesity epidemic through creating and implementing specific legislations to regulate food labels to discourage consumption of unhealthy snacks, as well as to prohibit food marketing targeted at children.